Clinical evaluation of postural posture of patients with previous stroke subjected to early rehabilitation - Sagan, Anna; Miler, Adrian; Podhorecka, Marta; Zukow, Walery (Journal of Education, Health and Sport, 2018)
<pre style="text-align: justify; background-image: initial; background-attachment: initial; background-size: initial; background-origin: initial; background-clip: initial; background-position: initial; background-repeat: initial;">Introduction: Impairment disorders are often found in patients with stroke and impairment of motor and cognitive functions. This is a very serious complication because, by imposing a motor impairment, it aggravates the condition of disability and makes it difficult to conduct physical rehabilitation. <pre style="text-align: justify; background-image: initial; background-attachment: initial; background-size: initial; background-origin: initial; background-clip: initial; background-position: initial; background-repeat: initial;">The resulting neurological deficits due to stroke determine functional disorders. The possibility of locomotion is usually compromised, therefore the risk of falls increases significantly. The aim of the work is to present Postural Assesment Scale for Strock PASS with the postural stroke assessment scale, the impact of early rehabilitation of patients staying in the neurology ward. <pre style="text-align: justify; background-image: initial; background-attachment: initial; background-size: initial; background-origin: initial; background-clip: initial; background-position: initial; background-repeat: initial;">Material and methods: Postural examination was carried out among 17 people, of which 8 were women, and 9 were male. The study was divided into two stages. The first stage occurred immediately after the stroke and the second one before the patient was discharged from the ward. Research was carried out at the Biegański Specialist Hospital in Grudziądz in the Department of Neurology and Clinical Neuroimmunology and Impact Department. <pre style="text-align: justify; background-image: initial; background-attachment: initial; background-size: initial; background-origin: initial; background-clip: initial; background-position: initial; background-repeat: initial;">Conclusions: The results of the postural studies carried out in people with previous stroke subjected to early physiotherapy have a beneficial effect of the conducted therapy. There are positive changes between the first and the final examination of the patients.